2016
DOI: 10.1080/2331186x.2016.1175051
|View full text |Cite
|
Sign up to set email alerts
|

Critical thinking and social interaction in active learning: A conceptual analysis of class discussion from Iranian students’ perspective

Abstract: Following the failures in traditional methods of teaching, theorists have recently emphasized students' active role in education in which the teacher is no longer a mere transmitter of knowledge. Discussion-based teaching has been regarded as a route to improving students' active role. The current study intended to discover the benefits of using discussion for social interaction and critical thinking disposition from Iranian students' perspective. Participants included 14 first-year educational psychology stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…It demonstrates that the students taught with think-pair-share strategy obtain the average score of pretest 2.16 and the average score of posttest 4.02. Previous research only focuses on implementing discussion strategy for the improvement of the Iranian EFL students as well as their critical thinking (Hajhosseini, Zandi, Hosseini Shabanan, & Madani, 2016). The results of the present study extend that critical thinking might mediate a better process of activating discussion strategy in the EFL classrooms.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…It demonstrates that the students taught with think-pair-share strategy obtain the average score of pretest 2.16 and the average score of posttest 4.02. Previous research only focuses on implementing discussion strategy for the improvement of the Iranian EFL students as well as their critical thinking (Hajhosseini, Zandi, Hosseini Shabanan, & Madani, 2016). The results of the present study extend that critical thinking might mediate a better process of activating discussion strategy in the EFL classrooms.…”
Section: Discussionsupporting
confidence: 76%
“…In the third step, the pairs share their responses/ideas with other pairs, other teams, or the entire group Yuliasri, (2013:15). Another relevant article about the Think-pair-share and speaking ability was conducted by some researches, such as Ardhy (2018), Hajhosseini (2016). Ardhy (2018) conducted research about the application of think-pair-share strategy in improving students' speaking ability.…”
Section: Think-pair-share Strategymentioning
confidence: 99%
“…This way is considered relevant because the present study makes an effort to cultivate learners' critical thinking skills in terms of solving social problems vis-a-vis Islamic radicalism in Indonesia which are brought into learning in the classrooms of Islamic education department. The effectiveness of CL based discussion has also been proven by Hajhosseini, Zandi, Shabanan, and Madani (2016). They revealed that CL in such a way supports learners' understanding in depth so that they continuously explore their thinking concepts.…”
Section: Discussionmentioning
confidence: 95%
“…The present study's findings supported the results of the previous studies that suggested that to develop critical thinking, lecturers must train it through discussion activities (Živkoviüa, 2016;Kalelioğlu & Gülbahar, 2014), persistent, thorough, and continuous reflection (Alotaibi, 2013;Akyuz & Samsa, 2009), seeking the best knowledge (truth-seeking) (Anshori et al, 2016) and exploration (Haghparast et al, 2013). Information-sharing activities through discussions and questions and answers were highly recommended in developing critical thinking because pre-service teachers could share, combine, and synthesize credible information (Kalelioğlu & Gülbahar, 2014;Hajhosseini, et al, 2016).…”
Section: Discussionmentioning
confidence: 99%